The role of autophagy on the differentiation potential of adipose stromal cell sheets under normoxia vs hypoxia - Pirraco, Rogério P. (2015)
It has been demonstrated that the effects of low oxygen tensions in cultures of human adipose stromal cells (hASC) range from increased cell death to changes in proliferation and differentiation potential. Specifically, hypoxia-induced autophagy promotes cell survival as result of Hypoxia Inducible Factor-1Î± activation and downstream signalling. In the present project, we intended to verify the existence of a correlation between the levels of hypoxia-induced autophagy and changes in the differentiation potential of hASC sheets. Cell sheets (CS) of hASC were produced and cultured in normoxic and hypoxic conditions (5% O2) for 1 to 4 days. At each time point, samples were collected for western blot and qPCR analysis or further cultured in osteogenic or adipogenic medium. Gene expression analysis of LC3, ULK1, BECLIN1 and ATG5 revealed overexpression of these autophagy players at day 4, independently of the culture oxygen tension. LC3II protein quantification revealed an increase in the autophagic flux at day 4, regardless of the oxygen tension, confirming the qPCR data. This suggests that the state of hyperconfluency of CS, increasing from day 1 to 4, may modulate the autophagic state of cells, masking the effects of low-oxygen tensions. Importantly, CS cultured in hypoxia for 4 days had increased osteogenic differentiation in comparison with day 1 hypoxic samples but decreased adipogenic differentiation, which hints at a possible correlation between higher levels of autophagy and a tendency towards the osteogenic phenotype. This hypothesis is being confirmed using autophagy modulators.